Material Characterization of Strontium Ferrite Powders for Producing Sintered Magnets by Ceramic Injection Molding (MagnetPIM) - Dietmar Drummer; Susanne Messingschlager (Advances in Materials Science and Engineering)
For this study, different strontium ferrite powders were mixed with a filling ratio of about 60 vol% in a binder system and formed into green compacts. During the process of injection molding, a magnetic field was generated in the tool via a magnetic coil, which enables magnetization and orientation of the ceramic particles. All powders were successfully processed by MagnetPIM. The investigations identified that it is impossible to extrapolate from the magnetic properties of a green compact to the magnetic properties of a sintered part. It became obvious, though, that, when producing very strong magnetic parts by MagnetPIM, the best results can be obtained by using powders with small particle sizes.